Ген SlWRKY33 cпособствует толерантности растений томата к солевому и водному стрессам - Гасымов, К.Г.; Наджафова, Л.А. (Физиология растений и генетика, 2014)
В данной работе идентифицирован и охарактеризован ген WRKY33 томата (Solanum lycopersicum L.), обозначенный как SlWRKY33. Он принадлежит к генам WRKY группы I и состоит из 1587 пн, ORF которого кодирует предполагаемый белок из 529 аминокислот. Исследование профилей экспрессии гена SlWRKY33 методами ОТ-ПЦР и гибридизации in situ показало значительное его индуцирование при воздействии засоления NaCl и в меньшей степени при водном дефиците. В цій роботі ідентифіковано і схарактеризовано ген WRKY33 томату (Solanum lycopersicum L.), позначений як SlWRKY33. Він належить до генів WRKY групи I і складається із 1587 пн, ORF якого кодує передбачуваний білок із 529 амінокислот. Дослідження профілів експресії гена SlWRKY33 методами ЗТ-ПЛР і гібридизації in situ виявило його значне індукування за дії засолення NaCl та меншою мірою за водного дефіциту. In this study a gene of the WRKY33 from the superfamily of WRKY factor designated as SlWRKY33, was isolated and characterized in tomato plants (Solanum lycopersicum L.). SlWRKY33, belonging to the Group I WRKY gene, consists of 1587 bp ORF, which encodes a putative protein of 529 amino acids. PCR analysis and in situ hybridization were performed to determine the expression pattern of SlWRKY33 under abiotic stresses — under the influence of elevated NaCl concentration and water deficit. Obtained results indicated a strong induction of SlWRKY33 under salinity, and to a lesser extent under water stress.